Pain from subcutaneous injections: myth or reality. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Srivastava, Leena; Robson, Peter
Abstract : Background: The use of the subcutaneous route is well established in Palliative Care. It is the most commonly used parenteral route for administering drugs when the oral route is not suitable. Based on 'clinical experience', it is often taught that subcutaneous injections are less painful; however, there is a paucity of evidence. Aim: The aim of this survey was to evaluate the incidence of pain from subcutaneous injections and explore the factors likely to influence pain. Method: A prospective survey was carried out at St Benedict's Hospice, Sunderland, UK in 2010 over a 1 month period. Data were collected for 50 consecutive injections, either given singly or via a subcutaneous cannula. Results: 76% of injections were not painful, 18% caused discomfort and 6% caused pain. 100% of injections causing pain were given singly. 45% of injections which were not painful were through subcutaneous cannulas. The insertion of subcutaneous cannulas did not cause pain. Limitations: Pain from subcutaneous injections is influenced by various concomitant factors and as our sample size was small, it was difficult to evaluate the specific role of individual factors. Moreover, all commonly prescribed drugs in Palliative care were not used. Discussion: This survey shows that most patients do not experience pain from subcutaneous injections. There was also a lower incidence of pain when a subcutaneous cannula was used for injections. There are currently no guidelines on the insertion of such cannulas. From our data, patients who need repeated injections will benefit from them early on. Conclusion: Our survey has shown that the majority of patients do not experience pain from subcutaneous injections. Further multicentre studies are needed to clarify the role of individual factors which may cause pain.